2021
DOI: 10.30880/ijie.2021.13.03.028
|View full text |Cite
|
Sign up to set email alerts
|

The Key Criteria in Deciding to Tender for Construction Projects

Abstract: Planning for a construction project is a formidable task which involves a huge investment with multiple stakeholders such as clients, consultants, and contractors. A tender is a submission of a technical, administrative, and contractual material made by a potential contractor in response to an invitation to tender by the project client. Established contractors normally realise the importance of doing initial research before committing themselves to enter the tender. Normally, tender pre-qualification is a stri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Bidding is a practice in which each project stakeholders try to minimize risk based on limited and incomplete tendering information (Adafin et al, 2016;Asgari et al, 2016;Bohari et al, 2021). Therefore, bidding strategy of each stakeholder is commercially sensitive, making it difficult to conduct honest and in-depth study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bidding is a practice in which each project stakeholders try to minimize risk based on limited and incomplete tendering information (Adafin et al, 2016;Asgari et al, 2016;Bohari et al, 2021). Therefore, bidding strategy of each stakeholder is commercially sensitive, making it difficult to conduct honest and in-depth study.…”
Section: Discussionmentioning
confidence: 99%
“…They argued that the inadequate quality of tender documents made it even more challenging for them to price projects appropriately. In the same vein, various studies (Laryea, 2011;Urquhart et al, 2017;Cheaitou et al, 2019;Bohari et al, 2021) have stated that major issues associated with tender documents are normally inappropriate or inadequate information. Zhou et al (2021) revealed different causes leading poor quality of tender documents including missing information, insufficient detail, impracticable design details, large blocks of provisional information that lacked detail.…”
Section: Quality Of Tender Documentsmentioning
confidence: 99%
“…'Detailed tendering document' is seen as having the highest significance level with a score of 4.84 and ranked 1 st . This corresponds to Bohari et al (2021), as they emphasize the need for detailed and high profile tender submission as low quality tender hampers contractor's chances. This is followed by submission of tender having the 2 nd most significant level which indicates that detailed tendering document and its submission is vital to contractor's chances of winning tenders.…”
Section: Evaluation Of the Identified Factors Significance Level (Bid...mentioning
confidence: 99%
“…Tendering provides a competitive way of getting contract award (Kog & Yaman, 2016). Open tendering system is the most used tendering system while carrying out construction procurement tendering (Bohari et al, 2021). According to Kog and Yaman (2016), there are fundamental tendering procedures which are open, negotiation and selective tendering.…”
Section: Factors Affecting Contractors' Decision To Tender For Constr...mentioning
confidence: 99%
See 1 more Smart Citation